Entomopathogenic Nematodes in Sustainable Food Production - Koppenhöfer, Albrecht M.; Shapiro-Ilan, David I.; Hiltpold, Ivan (Frontiers in Sustainable Food Systems, 2020)
The emphasis of this review is on the use and potential of entomopathogenic nematodes (EPNs) as biological control agents in sustainable food production across a wide range of agricultural and other commodities. To aid with the understanding of the potential of EPNs in sustainable food production, this review also provides overviews on EPN biology and ecology, mass production and application technology, and interactions with other management tools. First discovered in the 1920s, their commercialization as biopesticides in the 1980s was accompanied and followed by an exponential growth in research on their application, biology, and ecology, followed by a further expansion in more basic research areas since the mid-2000s. This review summarizes significant progress made in the research and application of EPN in insect pest management in important food crops including orchards, small fruit, maize, vegetables, tuber crops, greenhouses, and mushrooms. Significant factors affecting the success of EPN commercialization are also discussed. A growing interest in alternatives to synthetic insecticides and in organic agriculture opens opportunities for EPNs, but EPNs will need to be further improved with respect to efficacy, reduced costs, and ease of use. Moreover, their potential to recycle in host population beckons to be further exploited for long term pest suppression.